Pengaruh Makroekonomi dan Indeks Global terhadap Indeks Harga Saham Gabungan Selama Pandemi COVID-19 di Indonesia - Algia Artha; R.A. Sista Paramita (Jurnal Ilmu Manajemen, 2021)
The COVID-19 pandemic has affected many sectors, one of which is the capital market. The Coronavirus has claimed lives and can shake the order of life of a country. From an economic point of view, almost all countries experience a recession, a reduction in economic activity, increased unemployment, and a decline in people's purchasing power. This research examines the effect of the BI interest rate, exchange rate, inflation, SSEC index, KLSE index, SET index, and DJIA index on the Composite Stock Price Index. The research population is daily data during the COVID-19 pandemic in Indonesia from March 2020 to November 2020. The sampling technique uses purposive sampling. The number of samples is 111 data. The data analysis method uses multiple linear regression with IBM SPSS 25 software tools. The results show that the rupiah exchange rate against the US dollar has a negative effect and the Kuala Lumpur Stock Exchange has a positive effect on the Composite Stock Price Index, while the BI interest rate, inflation, SSEC index, the SET index and the DJIA index have no impact on the Composite Stock Price Index. However, all independent variables simultaneously affect the Composite Stock Price Index.